The Principal Agroecological Structure (PAS): a new tool for planning agroecosystems - Cleves-Leguízamo, José Alejandro; Toro-Calderón, Javier; Martínez-Bernal, Liven Fernando; León-Sicard, Tomás (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
This document presents, from the environmental prespective (ecosystem-culture relationships), the concept of the Principal Agroecological Structure (PAS) of agroecosystems, considered a dissipative structure. It discusses possible applications (resilience, production, and diversity) both inside and outside farms. The PAS can be useful in land use planning on farms, based on the concept of potential PAS, which allows for the quantification of the management of internal and external corridors, including natural vegetation. At the same time, it can be useful in the context of landscape management because it shows a series of cultural relationships (economic, social, symbolic and technological), hidden from the partial analysis of landscape ecology.